Resource misallocation in the presence of R&D spillovers - Kun Li; Helmuts Azacis; Kul Bahadur Luintel (Cardiff University, Cardiff Business School, 2023)
We study resource misallocation by explicitly modelling R&D input and knowledge spillovers. The effects of R&D and spillovers on firm-level productivity are extensively studied in applied work, but not in the context of resource misallocation. We establish that, in the presence of spillovers, efficient resource allocation requires that more productive firms face higher R&D input prices. Analysing UK firmlevel data, we find that the output gains from correcting misallocation are greatly overestimated when spillovers are ignored. Output losses due to capital distortions dominate those from labour and R&D inputs. Adopting a wrong R&D policy could lead to significant output losses.
Keywords: D24; D61; O30; O47; 330; resource misallocation; productivity; R&D spillover; the UK manufacturing firms